2014
DOI: 10.1111/tan.12334
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA‐B27 and ERAP1 with ankylosing spondylitis susceptibility in Beijing Han Chinese

Abstract: This study investigated the genetic polymorphisms of HLA-B27, together with polymorphisms on endoplasmic reticulum aminopeptidase 1 (ERAP1), and susceptibility for ankylosing spondylitis (AS) in the Beijing Han population. A case-control study was carried out for 602 AS patient samples and 619 matched controls of Han Chinese. HLA-B27 genotyping was performed by polymerase chain reaction-sequence specific primers (PCR-SSP), and four ERAP1 SNPs (rs27037, rs27980, rs27582, and rs27434) were selected and genotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…A literature search in the PubMed database resulted in the identification of 22 studies; 12 studies met the study inclusion criteria, including four studies from European populations and eight studies from Asian populations (two from Korean, six from Chinese populations), including the present study 9, 25, 26, 30, 31, 34, 35, 37, 38, 39, 40. Ten studies were excluded (seven studies due to lack of data and three studies having duplicate data).…”
Section: Resultsmentioning
confidence: 99%
“…A literature search in the PubMed database resulted in the identification of 22 studies; 12 studies met the study inclusion criteria, including four studies from European populations and eight studies from Asian populations (two from Korean, six from Chinese populations), including the present study 9, 25, 26, 30, 31, 34, 35, 37, 38, 39, 40. Ten studies were excluded (seven studies due to lack of data and three studies having duplicate data).…”
Section: Resultsmentioning
confidence: 99%
“…A previous genome-wide association study revealed that ERAP1 polymorphisms are associated with AS at a high level of statistical significance [3], but more recent studies, in different ethnic groups, have produced mixed results [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In our previous meta-analysis, we found that the rs27044, rs17482078, rs10050860, rs30187, and rs2287987 polymorphisms of ERAP1 were associated with the development of AS in Europeans [28].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were excluded because one used the data analyzed in another study and another did not have extractable allele data. Thus, 20 studies met the inclusion criteria (Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]27]. However, one of these studies contained data on three groups [13] and two studies had data on two different groups [17].…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Research on correlation between HLA-B27 subtypes and AS showed that HLA-B*27:04, B*27:05, and B*27:02 were highly detected in Beijing Han population [29], and Qi J et al discovered that AS patients with HLA-B*2705 demonstrated an older age of onset and had a higher risk of uveitis and dactylitis than did AS patients with HLA-B*2704 [30]. Further researches were required to explore the association between SpA-related uveitis and HLA-B27 subtypes.…”
Section: Discussionmentioning
confidence: 99%